Factors of psychological readyness for real estate activity - Bielik, Nataliia (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2020)
The topic's relevance is related to the situation in the labor market, which needs competent realtors. The aim is to study and investigate the main factors of the psychological readiness towards realtor professional activity. The article considers the main approaches to studying the phenomenon of psychological readiness and factors of its functioning. Psychological readiness for real estate activity is an integrated quality of personality, which aims to an adequate reaction to the possibilities of a situational solution of universal professional problems of a realtor utilizing acquired professional competencies. The study involved 130 people. The methods employed in the present study include various types of questionnaires, namely Guilford's Test (J. Guilford); Big Five / 5PFQ (P. Costa & R. McCrae), Gertsberg Test (F. Hertsberh); Test Diagnostics of personality's socio-psychological attitudes in the motivational-needs sphere (O. F. Potomkin); Schwartz value survey (S. Schwartz); Professional activity motivation (K. Zamfir in A. Rean's modification); Diagnostics of motivational orientations in interpersonal communications (I. Ladanov, V. Urazaieva); Study of volitional self-regulation (A. Zvierkov, E. Eidman).The factors of psychological psychological readiness for professional activity as realtors were revealed: "standardness", "humanism", "pragmatism", "altruism", "endurance", "power", and "practicality". The main characteristics (competencies) of a specialist realtor include: a) the ability to solve complex problems and problems in the process of work (integral competence); b) the ability to apply knowledge in practical situations; ability to generate new ideas; ability to identify, formulate and solve problems; appreciate and respect diversity and multiculturalism; ability to act on the basis of ethical considerations (motives); ability to act socially responsibly and consciously; ability to develop and manage projects; ability to motivate people and move towards a common goal (general competencies); c) the ability to identify, analyze and interpret the information series of the realtor profession, identify problems and suggest ways to solve them; the ability to demonstrate an understanding of the patterns and features of human functioning in the context of the transaction in the context of professional tasks; ability to offer creative ways to solve professional problems, to make professionally correct decisions and to implement them (special competencies).
Keywords: psychological readiness towards realtor professional activity; factors of professional activity; factors of the readiness towards realtor professional activity